2015
DOI: 10.1186/s40064-015-0988-5
|View full text |Cite
|
Sign up to set email alerts
|

Taxane-cisplatin-fluorouracil as induction chemotherapy for advanced head and neck cancer: a meta-analysis of the 5-year efficacy and safety

Abstract: BackgroundThe objective of this study was to compare the efficacy and safety of taxane (docetaxel or paclitaxel), cisplatin, and fluorouracil (Tax-PF) with cisplatin plus fluorouracil (PF) regimen by a meta-analysis of data retrieved from the literature.MethodsSeven randomized clinical trials were identified, which included patients with advanced head and neck cancer who underwent induction chemotherapy with either a Tax-PF or PF protocol. The outcomes included the 3-year and 5-year overall survival (OS) and p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Other modified designs reached comparable results, with ORRs of up to 100% (6). In a recent meta-analysis, seven clinical trials that investigated 3-and 5-year efficacy were reviewed, and ORR was found to be better in the TPF induction chemotherapy group compared with that in the PF-based therapy group (8). In the present retrospective study, an ORR of 86% was achieved; therefore, the data are comparable with the results of already published reports.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Other modified designs reached comparable results, with ORRs of up to 100% (6). In a recent meta-analysis, seven clinical trials that investigated 3-and 5-year efficacy were reviewed, and ORR was found to be better in the TPF induction chemotherapy group compared with that in the PF-based therapy group (8). In the present retrospective study, an ORR of 86% was achieved; therefore, the data are comparable with the results of already published reports.…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with other clinical trials, hematological and non-hematological treatment-related side effects (particularly grade 3 and 4 leukopenia and gastrointestinal reactions) were observed in nearly all investigated patients (5,6,8,18,19). Another concern is the high rate of neutropenia during chemotherapy with TPF.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations